Effect of early postpartum EMDR on reducing psychological complaints in women with a traumatic childbirth experience - Emma H. M. Kopmeiners; Martine H. Hollander; Nicole van Voorst; Claire A. I. Stramrood (Taylor & Francis Group, 2023)
This pilot study investigated the feasibility of postpartum Eye Movement Desensitization and Reprocessing (EMDR) for improving posttraumatic stress disorder (PTSD) symptoms, and its association with work absence, relationship difficulties, and development of psychiatric disorders in women with a traumatic childbirth experience who do not meet all criteria for PTSD. A randomized controlled study was conducted among 20 women (EMDR (N=11) vs. care as usual (CAU) (N=9)) who reported a traumatic birth. Outcomes were measured by questionnaires and a semi-structured interview. The results showed improvement of trauma-related psychological complaints for all women. EMDR appears to be more effective in reducing PTSD symptoms than CAU. Moreover, EMDR showed a small positive effect on work absence due to factors related to the traumatic childbirth experience. Results from the questionnaires were substantiated by interviews. However, due to the small size of the study, no statistically significant differences were found. In addition, no differences were found for relationship difficulties and development of psychiatric disorders. In conclusion, women with a traumatic birth experience may benefit from EMDR, even if they do not qualify for a diagnosis of PTSD. This study could be a starting point for future research aimed at early treatment that reduces trauma-related psychological complaints in postpartum women.